Third stage of labour: expectant versus active management-a comparative study in local low risk population - Chandnani, Kavita A.; Sharma, Deepti D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Postpartum haemorrhage (PPH) is the leading cause of maternal mortality, accounting for about 35% of all maternal deaths. These deaths have a major impact on the lives and health of the families affected. Thus, anticipation as well as proper management of 3rd stage of labour is mandatory. The objective of this study was to compare expectant and active management of third stage of labour in preventing post-partum blood loss and having impact on prevention of maternal mortality in local population. Advantages and disadvantages of both techniques might be over estimated. Methods: Prospective comparative study carried out in Obstetrics and Gynecology department of SBKSMIRC (Shrimati Bhikhiben Kanjibhai Shah Medical Institute and Research Centre), Dhiraj general hospital, comprising of 200 laboring women admitted directly or from OPD to labour room for expected vaginal delivery. They were randomly allocated to group A (expectant management) and group B (active management). Labour progress was charted on partograph and interventions recorded. Statistical analysis of data was done after compiling and tabulation of data. Mean±SD for descriptive variables were calculated and appropriate statistical tests applied to determine significance. Results: Average PPBL (post-partum blood loss) was 360.5ml in group A as compared to 290.6ml in group B. 12 patients in group A had blood loss more than 500ml while none in group B. 66% cases in group B had duration of third stage of labour less than 5 min as compared to only 22% in group A. the mean duration of third stage was 13.46±8.3 in group A while 5.32±3.05 in group B. these differences were statistically significant. Conclusions: Active management of the third stage of labour is associated with less blood loss as well as a shorter duration of third stage compared with expectant management. It is reasonable to advocate this regime.